Some Common Fixed Point Results for Rational Type Contraction Mappings in Complex Valued Metric Spaces. (3rd June 2013) - Chandok, Sumit; Kumar, Deepak
Abstract : We prove some common fixed point theorems for two pairs of weakly compatible mappings satisfying a rational type contractive condition in the framework of complex valued metric spaces. The proved results generalize and extend some of the known results in the literature.